THE EFFECT OF KNOWLEDGE ON VOTING INTEREST PRODUCTS PT. MANDIRI SHARIA BANK PADANGSIDIMPUAN (Case Study to Guru Al-Azhar Bi'ibadillah Ujung Gading District Angkola stem) - Elna Sriwanna; ikhwanuddin harahap; Windari windari; ali hardana (Institut Agama Islam Negeri Padangsidimpuan, 2020)
This research is motivated by the assumption that some Al Azhar Bi'ibadillah teachers say that there are no differences between Islamic banks and conventional banks. Besides that, the socialization carried out by Islamic Banks, especially PT Bank Syariah, is still low. The formulation of the problem in this study is whether there is an influence of knowledge on the interest in choosing PT Bank Syariah Mandiri Padangsidimpuan products on the teacher of AlAzhar Bi'ibadillah Ujung Gading, Batang Angkola District. This study aims to determine the effect of knowledge on the interest in choosing PT Bank Syariah Mandiri products in Padangsidimpuan in Al-Azhar Bi'ibadillah Ujung Gading Teachers, Batang Angkola District. The purpose of this research is to add insight to researchers and provide information and knowledge about Islamic banking for Al Azhar Bi'ibadillah teachers.This research is quantitative with a simple linear regression, sampling using census techniques also called saturated sampling techniques, with a population of 49 and 49 samples, using the help of SPSS Version 22 program. Based on the results of the test of the coefficient of determination (R2) it can be seen that the R Square value of 0.121 means that the knowledge variable is able to explain the variable of interest by 12% while the remaining 88% is explained by other variables not included in this model. In another sense that there are still variables that affect the interest in choosing PT Syariah Syariah Mandiri products in addition to knowledge. Based on the results of this study indicate the influence of knowledge of interest with the value of tthitung (2.544 ˃ 2.012).